Glutamate and excitotoxicity in central nervous system disorders: ionotropic glutamate receptors as a target for neuroprotection - Jorge Y. Magdaleno Roman; Christian Chapa González (Neuroprotection, 2024)
Abstract Recent advances in neuroscience have illuminated the central role of glutamate dysregulation in various neurological disorders. The glutamatergic system has emerged as a central player in the pathophysiology of various neurological disorders. The dysregulation of glutamate signaling, leading to excitotoxicity and neuronal cell death, has been a focal point in understanding the underlying mechanisms of these conditions. This has prompted a paradigm shift in neuroprotection research, with a growing emphasis on targeting ionotropic glutamate receptors (iGluRs) to restore glutamatergic homeostasis. This review provides a comprehensive overview of recent advancements in the field of iGluR‐targeted neuroprotection. We further investigate the implications of glutamate dysregulation in the central nervous system (CNS) disorders, highlighting the complex interplay between excitotoxicity and neuroprotection. We elucidate the multifaceted factors that render neurons vulnerable to excitotoxic damage, emphasizing the need for innovative therapeutic approaches. This review provides an extensive survey of the burgeoning field of iGluR‐targeted neuroprotection. It showcases the significant potential of a wide array of compounds, encompassing both natural and synthetic agents, to modulate iGluRs and ameliorate excitotoxicity and oxidative stress‐induced neuronal damage. These compounds have demonstrated impressive neuroprotective effects in diverse experimental models, from glutamate‐induced toxicity to traumatic brain injuries. We advocate for further research and clinical investigations to harness the full therapeutic potential of iGluR modulation, heralding a promising era in neuroprotection and CNS disorder management.